Language Skills Needs, Language Competence, and Readiness for Self-Directed Learning Among Nonnative Speaking Teachers Of Arabic Language - Adam Kheir, Abdalla Mohamed (2005)
The present study aims at: (a) determining Arabic teachers' extent of needs for language skills, (b) perceived competence in using language skills, and (c) readiness for self-directed learning. Two groups of Arabic teachers, namely, non-native government religious schoolteachers (Sekolah Menengah Kebangsaan Agama SMKA) and non-native speaking teachers of Arabic of the Matriculation Center International Islamic University Malaysia (IIUM), were involved in the study. Approximately, 160 respondents were involved in the study, 70% were religious schoolteachers and 30% were teachers of the Matriculation Center IIUM. A questionnaire was employed to gather data. The results of data analysis indicated that both schoolteachers and the Matriculation teachers showed high level of needs for language skills, their perceived language competence was also high, but they showed moderate level of readiness for self-directed learning. They perceived lower in benefiting from external learning factors such as learning resources and learning strategies. Schoolteachers showed higher level of need in language skills, language competence and readiness for SDL compared to Matriculation teachers. Benefiting from external learning factors however, was lower for schoolteachers compared to Matriculation. The results of t-test and ANOVA indicated no significant difference between Arabic teachers' needs for language skills and language competence in terms of their training, majors and qualifications. However, there is a significant difference in readiness for selfdirected learning in terms of training, but no significant difference in terms of majors and qualifications. The results of stepwise multiple regression analysis demonstrated a significant correlation of three independent variables namely, learning strategies, language competence and teaching experience, with the dependent variable readiness for SDL. The findings of the study suggest that any effort by the educational authority to assist Arabic teachers for their self development has to take into account their needs, ways to enhance their language competence and ways to improve their readiness for SDL.